2019
DOI: 10.1186/s12913-019-4494-2
|View full text |Cite
|
Sign up to set email alerts
|

EQUIP Emergency: study protocol for an organizational intervention to promote equity in health care

Abstract: Background Social inequities are widening globally, contributing to growing health and health care inequities. Health inequities are unjust differences in health and well-being between and within groups of people caused by socially structured, and thus avoidable, marginalizing conditions such as poverty and systemic racism. In Canada, such conditions disproportionately affect Indigenous persons, racialized newcomers, those with mental health and substance use issues, and those experiencing inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
65
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(69 citation statements)
references
References 45 publications
4
65
0
Order By: Relevance
“…It fails to recognise individual patient characteristics, dynamic interactions and institutional context factors that may lead a clinician to make certain management decisions. The use of clinical vignettes may not accurately reflect the decisions made in the ED where physician fatigue, patient burden, time pressures and lack of clinical information may result in prejudiced patient management 2,11 . Clinical vignettes may also be prone to response bias, where participants provide a more socially desirable response than what they would do in clinical practice 23 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It fails to recognise individual patient characteristics, dynamic interactions and institutional context factors that may lead a clinician to make certain management decisions. The use of clinical vignettes may not accurately reflect the decisions made in the ED where physician fatigue, patient burden, time pressures and lack of clinical information may result in prejudiced patient management 2,11 . Clinical vignettes may also be prone to response bias, where participants provide a more socially desirable response than what they would do in clinical practice 23 .…”
Section: Resultsmentioning
confidence: 99%
“…Indigenous communities continue to suffer adverse experiences in healthcare, which can be partly attributed to ongoing institutional racism, 5 and reinforced by structural inequities in housing, education, employment and incarceration 5 . Indigenous peoples are less likely to access appropriate care and often receive lower quality care 2,5 . Although there are currently no existing studies looking at implicit bias of healthcare workers towards Indigenous Australians, one very large study found most Australians carry an implicit bias towards Aboriginal and Torres Strait Islander peoples 33 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, we propose that all ED staff, from leadership to physicians to triage nurses to registration and janitorial staff, be supported in training around the principles of TVIC. TVIC has been demonstrated as having an impact on health outcomes in primary care, and work is currently being done to study this in the ED context [16,36]. Enhancing awareness of all team members of the prevalence of ACEs and trauma, as well as the impact that ACEs may have on patients' presentations, mental health, coping mechanisms and interpersonal interactions, can enhance both provider and patient experience by reducing negative encounters.…”
Section: Discussionmentioning
confidence: 99%